Looking Inward to 21st Century Pedagogy - Doerksen, Rose (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
Through the lens of a student, this Note from the Field responds to a historical research project which engages pre-service teachers in critical citizenship and social imagination. Looking inward facilitates a personal learning experience of identity that is applied to learning in the 21st century. When 21st century pre-service teacher education looks inward rather than forward and outward, we learn to live in the 21st century rather than envision it.